As Diuinae Institutiones de Lactâncio e a construção da identidade de um Império Cristão (séculos III-IV) - Gobato, Douglas Raphael Machado (2016)
In the context of the crisis that manifested itself since the end of the second century, Lactantius composed his Diuinae Institutiones contesting the charges leveled against the followers of Christ by the Roman State. Using your experience in the field of rhetoric, directs his apology to cultured segments of society, seeking to dissuade them of the precepts disseminated by Hellenistic culture and bring them to acceptance of Christianity. Being a roman citizen, he was not opposed political institutions of the Empire, on the other hand, shared the apocalyptic tradition that saw at the adversity that moment the signs of the end times approached. Refuting polytheistic beliefs and the teachings of philosophy, he proposes the conversion of Rome to Christianity as the only hope to delay the divine judgment. In this sense, we analyze the process of building a new imperial identity, debased by north african author in his main work